Cryotherapy, breeding instrument, commercial stock deposit: Cryopreservation is more than a long term conservation tool for of plant genetic resources - Panis, Bart (2024)
Cryopreservation is considered as safest long term conservation methodology for vegetatively propagated, sterile or recalcitrant seed producing crops and trees. Well known examples of cryopreserved collections are apple, bananas, potato, mulberry and garlic that have each more than 1000 accessions stored in liquid nitrogen. Currently, between 20.000 and 25.000 accessions of wide variety of species are safely preserved in liquid nitrogen and more initiatives to increase these numbers are in the pipeline. Cryopreservation can, however, also be applied as a tool in classical as well as modern breeding initiatives. For example, for many adult trees (such as conifers) clonal propagation is only possible through somatic embryogenesis (starting from seeds). After breeding, it takes, however, decades before the value of a selection/cross of a tree can be determined. The storage of embryogenic cultures could meanwhile happen through cryopreservation. As an example as modern breeding tool, cryopreservation is applied to store thousand cryotubes containing transformation competent cell lines of banana. For many crops such as banana, sweet potato, grapevine and potato cryopreservation is also used for pathogen eradication. This effect of cryotherapy is not based on killing pathogen such as viruses, phytoplasmas and bacteria by freezing but on the selection of the most meristematic part of the plant that has also the highest chance to be free of those pathogens. Finally, cryopreservation can also be applied to store large amounts of independent in vitro cultures that are being produced and conserved by in vitro production companies.